Overhang constraint for topology optimization of self-supported compliant mechanisms considering additive manufacturing. (April 2019) - Garaigordobil, Alain; Ansola, Rubén; Veguería, Estrella; Fernandez, Igor
Abstract: This work presents a computational procedure for direct integration of Topology Optimization and Additive Manufacturing (AM) technologies for compliant mechanisms design. Many topologically optimized geometries present manufacturing problems derived from the lack of self-supporting capacities and require sacrificial support material for 3D printing. The proposed strategy introduces a novel overhang constraint to control the amount of sacrificial support material required for additive manufacturing of compliant mechanisms. This overhang constraint is defined as the ratio between the value of self supported contours and the total amount of admissible and inadmissible contours, and is computed by an edge detection algorithm known as the Smallest Univalue Segment Assimilating Nucleus, that analyzes the geometry of the model for locating contours and computes their inclination and orientation. The proposed algorithm has been implemented as part of a software for computer aided design and several benchmark examples have been used to demonstrate the capacities of the approach. Highlights: A computational procedure for designing optimum topologies of self-supporting compliant mechanisms is presented. A new global overhang constraint is proposed to control the inclinations of the boundaries and enhance support-free Additive Manufacturing. An efficient approach to find compromise solutions between support structure and compliant mechanism performance. Efficient contour detection and analysis by means of the Smallest Univalue Segment Assimilating Nucleus(SUSAN) algorithm.